2015
DOI: 10.1111/jai.12891
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gradual or abrupt changes in salinity on digestive enzymes activity of Caspian kutum,Rutilus kutum(Kamensky, 1901) larvae

Abstract: This study investigates the effects of gradual or abrupt changes in rearing salinity on food transit time and digestive enzymes activity of Caspian kutum (Rutilus kutum) larvae. The larvae (532 AE 0.05 mg) were supplied and randomly allocated into 12 tanks at a density of 45 fish per tank. Experimental treatments were fresh water (salinity 0) [FW] as control, exposure to salinity 5 [T 1 ], and gradual transfer to salinity 10 in two steps of first to 5 h, then and after 12 h to a salinity of 10 [T 2 ], and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In this study, TRYP in the LS group was significantly up-regulated compared with the HS group after overwintering. A similar report has found that low salinity has a positive effect on TRYP in Rutilus kutum (Gheisvandi et al, 2015).…”
Section: Characterization Of Mrna-level Protein Expression In Metabolismsupporting
confidence: 61%
See 1 more Smart Citation
“…In this study, TRYP in the LS group was significantly up-regulated compared with the HS group after overwintering. A similar report has found that low salinity has a positive effect on TRYP in Rutilus kutum (Gheisvandi et al, 2015).…”
Section: Characterization Of Mrna-level Protein Expression In Metabolismsupporting
confidence: 61%
“…In this study, TRYP in the LS group was significantly up‐regulated compared with the HS group after overwintering. A similar report has found that low salinity has a positive effect on TRYP in Rutilus kutum (Gheisvandi et al, 2015). It has also been found that TRYP mRNA expression in Litopenaeus vannamei was highest at low‐salinity levels (Gao et al, 2016).…”
Section: Discussionmentioning
confidence: 57%
“…Digestive enzymes depict the overall digestion process and nutritional status of fish (Bolasina et al, 2006; Haque et al, 2021). In teleosts, several studies demonstrated that intestinal enzyme activity changes with salinity (Bolasina et al, 2007; Gheisvandi et al, 2015). In the present study, high digestive enzyme activity observed at higher salinities (9 and 12 ppt) compared with lower ones (T2 and T3) and freshwater T1 (0 ppt) group.…”
Section: Discussionmentioning
confidence: 99%
“…Limited knowledge exist about influence of hyperosmotic or isosmotic salinity on early pike perch larval ontogeny or physiology. Environmental changes in salinity have shown to result in modification of physicochemical conditions of the gut lumen in other fish larvae and may exert a direct action on digestive enzyme performance (Boef and Payan, 2001) as well as food transition time (Gheisvandi et al, 2015), that may have implications on growth performance.…”
Section: Accepted Manuscriptmentioning
confidence: 99%